2010
DOI: 10.1080/10570314.2010.512279
|View full text |Cite
|
Sign up to set email alerts
|

Messages About Weight Management: An Examination of How Acceptance and Challenge Are Related to Message Effectiveness

Abstract: A confirmation perspective was employed to assess weight management messages individuals receive from significant others. Confirmation was conceptualized as having two components: acceptance and challenge. Both were hypothesized to predict message effectiveness. Study 1 explored types of weight management messages and how they varied in acceptance and challenge. Study 2 showed effective messages had higher acceptance and challenge than ineffective messages. Further, acceptance and challenge in hypothetical mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 58 publications
2
24
2
Order By: Relevance
“…Participants rated their friends' responses during co-rumination using the Dailey, Romo, and McCracken (2010) 10-item acceptance scale measuring friends' attentiveness and warmth during interactions (e.g., "When I mention something about my body/weight, my friend typically shows she understands how I feel about my weight").…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants rated their friends' responses during co-rumination using the Dailey, Romo, and McCracken (2010) 10-item acceptance scale measuring friends' attentiveness and warmth during interactions (e.g., "When I mention something about my body/weight, my friend typically shows she understands how I feel about my weight").…”
Section: Methodsmentioning
confidence: 99%
“…Dailey and colleagues (Dailey, Richards, & Romo, 2010;Dailey, Romo, & McCracken, 2010;Dailey, Romo, & Thompson, 2011) investigated the content of weight-related communication with others in effort to understand the most effective ways partners can help each other feel confirmed about their body and weight. Their research found that during conversations about weight management, romantic partners/spouses, friends, parents, and siblings frequently made reassuring comments ("You're much slimmer than you seem to think.…”
Section: Confronting Co-rumination: Confirmation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This recent application of confirmation theory isolates two components of confirmation—acceptance and challenge (e.g., Dailey, McCracken, & Romo, 2011; Dailey, Richards, & Romo, 2010; Dailey, Romo, & McCracken, 2010). Acceptance is defined as the degree to which a relational partner shows positive regard, care, warmth, and attentiveness during interactions regarding WM.…”
Section: Confirmation and Weight Managementmentioning
confidence: 99%
“…Further, one study found that the combination of acceptance and challenge from significant others during interactions about weight management was associated with the highest levels of body esteem and healthy eating behaviors among college students and members from the community (Dailey, Richards, & Romo, ). However, such interaction effects were not observed in predicting perceived message effectiveness in promoting healthy eating and exercise behaviors (Dailey, Romo, & McCracken, ).…”
Section: Background Literaturementioning
confidence: 99%